De mãe para filha : a transmissão da violência doméstica entre gerações e a trajetória de vitimização entre mulheres - Angélica Pereira dos Santos (2021)
This work aimed at to investigate the influence of domestic violence transmission among different generations in the same nuclear family. It focuses on the trajectory of the target-individual, that is, women over eighteen years old who, as well as their mothers, suffered of physical violence, sexual and/or psychological in a heterosexual intimate or marital relationship. To this end, the qualitative method of in-depth interviews, focused on a retrospective approach to this woman's life, was used. The employment of this method delivered relevant results. First of all, the confluence of the trajectories of mothers and daughters was verified in the experience of violence events with an intimate partner, or in the reproduction of behaviors and roles associated with the female that reinforce victimization. Second, the reproduction of behaviors and the violence witnessed lead to the development of a helplessness learned situation, which is a consequence of trauma and recurrent pain situations that make the cycle of violence even more difficult to be broken. Finally, the relationship among the reproduction of violence events and the life course of the victims is observed, with emphasis on cases of bullying and racism. Those aspects, in addition to events of violence in the nuclear family that directly affected the self-esteem and self-confidence of these women, influence negatively in intimate relationships. In this way, the creation of public policies focusing at indirect victims of domestic violence is recommended, as well as actions for solving the continuum of violence that crosses the lives of many women and girls.